2017
DOI: 10.1002/ecs2.1654
|View full text |Cite
|
Sign up to set email alerts
|

Climate and herbivore influence on Vaccinium myrtillus over the last 40 years in northwest Lapland, Finland

Abstract: Abstract. Annual fluctuations in the abundance of wild berries have repercussions on animals and humans who depend on this important resource. Although studies have tried to disentangle the effect of climate and herbivores on inter-annual berry yield, there are still many uncertainties as to which factors are driving productivity. In this research, we evaluated the effect of climate and predation by rodents and moths on the abundance of bilberry (Vaccinium myrtillus) flowers and berries at the Kilpisj€ arvi Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…High flower density around Vaccinium plants may lure pollinators away from the Vaccinium flower, as suggested by the floral market hypothesis, but could also draw pollinators into the area that otherwise would not have visited [37]. Pollen availability explained the most variation in Finnish bilberry (V. myrtillus) fruit production models [38]. Given the overall low pollinator availability in black spruce forests [34,39], we expected plants in neighborhoods with high total floral resources to have greater pollen loads and lower pollen limitation than those in neighborhoods with low total floral resources.…”
Section: Introductionmentioning
confidence: 93%
“…High flower density around Vaccinium plants may lure pollinators away from the Vaccinium flower, as suggested by the floral market hypothesis, but could also draw pollinators into the area that otherwise would not have visited [37]. Pollen availability explained the most variation in Finnish bilberry (V. myrtillus) fruit production models [38]. Given the overall low pollinator availability in black spruce forests [34,39], we expected plants in neighborhoods with high total floral resources to have greater pollen loads and lower pollen limitation than those in neighborhoods with low total floral resources.…”
Section: Introductionmentioning
confidence: 93%
“…Light availability commonly limits plant fitness by influencing the rate of photosynthetic carbon gain [59,62] and the activity of pollinators [13,29]. Ultimately, however, life history determines whether increased light availability will affect fruit production [63,64].…”
Section: Positive Effect Of Light Availability On Flower and Fruit Prmentioning
confidence: 99%
“…Light availability in other species has been correlated with flower number [19,26], thereby limiting fruit and seed formation by setting a limit on the number of fruits that can potentially mature [11]. Since light availability is correlated with air temperature and air humidity [27,28], measures of light availability may be a proxy for conditions that may also affect pollinator activity [13,29,30]. Previous studies have shown that fruit production in buffaloberry is affected by light and pollen availability [7,8], as is the case for other angiosperms [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, forest management, history and stand age affect the abundance (Hedwall et al 2013;Eldegard et al 2019) and fruit production of bilberry (Nielsen et al 2007;Miina et al 2009). Moreover, the fruit production of bilberry is dependent on numerous climate-related factors (Selås et al 2015;Boulanger-Lapointe et al 2017), leading to a high between-year variation in bilberry yields. Intensive berry picking by rakes may cause damage by ripping and removing the biomass of bilberry comparable to herbivory.…”
Section: Introductionmentioning
confidence: 99%